1994
DOI: 10.1139/b94-156
|View full text |Cite
|
Sign up to set email alerts
|

Somatic polymorphism in the achenes of Tragopogon dubius

Abstract: Achenes of Tragopogon dubius have previously been described as dimorphic with respect to size and colour. In this investigation we found that there is a continuum of weight change from lighter central achenes to the heavier peripheral achenes. The main component of change is the pericarp. Outer achenes may also contain larger quantities of phenolic compounds than inner achenes. The differences in mass, morphology, and chemical characteristics may be significant enough to result in differences in germination be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
0
24
1
1
Order By: Relevance
“…Our results show that in these three species of Anacyclus, achene size is related to position on the capitulum, so that outer achenes are significantly heavier than inner ones, as commonly occurs in other heterocarpic Asteraceae (McEvoy, 1984;Venable & al., 1987;McGinley, 1989;Maxwell & al., 1994;Imbert & al., 1996;Imbert, 2002;Brändel, 2007;Sun & al., 2009;Filho & Takaki, 2011; but see Rocha, 1996). Usually, in such heterocarpic species, variation in achene size and position is also correlated to the presence or absence of dispersal structures within the same capitulum.…”
Section: Achene Size and Morphology: Their Implications In Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that in these three species of Anacyclus, achene size is related to position on the capitulum, so that outer achenes are significantly heavier than inner ones, as commonly occurs in other heterocarpic Asteraceae (McEvoy, 1984;Venable & al., 1987;McGinley, 1989;Maxwell & al., 1994;Imbert & al., 1996;Imbert, 2002;Brändel, 2007;Sun & al., 2009;Filho & Takaki, 2011; but see Rocha, 1996). Usually, in such heterocarpic species, variation in achene size and position is also correlated to the presence or absence of dispersal structures within the same capitulum.…”
Section: Achene Size and Morphology: Their Implications In Dispersalmentioning
confidence: 99%
“…Apart from these exceptions, most of achene variation is found within capitula. Besides variation in morphology, achenes may also vary markedly in size (Venable & al., 1987;McGinley, 1989;Maxwell & al., 1994;Imbert & al., 1996;Van Mölken & al., 2005;Brändel, 2007 ly the heaviest ones, whereas those adapted for greater dispersal are generally lighter (McEvoy, 1984;Tanowitz & al., 1987;Venable & al., 1987;Imbert & al., 1996;Imbert & Ronce, 2001;Brändel, 2004Brändel, , 2007Bastida & Menéndez, 2004, Bastida & al., 2010 among others). With regard to germination performance, recent research suggests that variation in achene size may be the main driver of divergent behavior exhibited by seeds from different achene morphs (Van Mölken & al., 2005;Torices & Méndez, 2010).…”
mentioning
confidence: 99%
“…Heavier, darker seeds, with a higher concentration of phenolic compounds, are produced from the outer ring of florets on the receptacle (Maxwell et al 1994). Because the number of dark seeds per flower varies considerably (from 4 to 33), it has been speculated that the production of dark seeds may vary according to resource availability.…”
Section: Reproductionmentioning
confidence: 99%
“…It has been observed that flower heads with a larger total seed weight allocate proportionally less biomass to dark seeds (McGinley 1989). Maxwell et al (1994) found seed weight increased continually from the central to peripheral achenes. The embryo made up proportionally less of the total seed mass in the central seeds.…”
Section: Reproductionmentioning
confidence: 99%
“…Both extreme (outermost and innermost) fruit types drastically differ in their shape, length, colour, weight, ultrasculpture, or details of anatomy (Voytenko 1981), as well as abscission pattern (Green & Quesada 2011), although the achenes in an intermediate position on the receptacle are characterized by morphological and anatomical structure transitional between that of the outer and inner achenes (Voytenko 1981, Maxwell et al 1994. The lower weight of the central achenes in Tragopogon correlates with a greater long-range dispersal in comparison to the outer achenes which have mostly atelechoric dissemination (Voytenko 1981).…”
Section: Introductionmentioning
confidence: 99%